Effects of low barometric pressure on the ram semen - Ferruccio Accame, O. (1945)
Cited literature showing that low barometric pressures produce a cessation of spermatogenesis in fertile animals brought to the task. There were no data on the effect of pressure changes on the semen when it is sent from one height to another major. Six rams (two Hampshire two Rambouillet a Merino and Dorset Horn) was used to study the effect of low barometric pressures semen exposure occurred during different time periods. EI semen was subjected to pressures equivalent to 12,000 (3,660) and 20,000 feet (6,100 mts.) High during periods ranging from several minutes to 17 hours. Motility was not affected by low barometric pressure. The height had no effect on the proportion of abnormal sperm in the semen. EI percentage of live spermatozoa was not influenced by low barometric pressures. The hydrogen ion concentration was not affected by low pressures. According to the results, ram semen was not affected by altitude. More research, particularly on the fertilizing capacity of sperm subjected to reduced barometric pressure is needed.